Genomic affinities revealed by GISH suggests intergenomic restructuring between parental genomes of the paleopolyploid genus Zea - González, Graciela Esther (2015)
The present work compares the molecular affinities, revealed by GISH, with the analysis of meiotic pairing in intra-and interspecific hybrids between species of Zea obtained in previous works. The joint analysis of these data provided evidence about the evolutionary relationships among the species from the paleopolyploid genus Zea (maize and teosintes). GISH and meiotic pairing of intraspecific hybrids revealed high genomic affinity between maize (Zea mays subsp. mays) and both Zea mays subsp. parviglumis and Zea mays subsp. mexicana. On the other hand, when Zea mays subsp. huehuetenanguensis DNA was probed on maize chromosomes, a lower affinity was detected, and the pattern of hybridization suggested intergenomical restructuring between the parental genomes of maize. When DNA from Zea luxurians was used as probe, homogeneous hybridization signals were observed through all maize chromosomes. Lower genomic affinity was observed when DNA from Zea diploperennis was probed on maize chromosomes, especially at knob regions. Maize chromosomes hybridized with Zea perennis DNA showed hybridization signals on four chromosome pairs: two chromosome pairs presented hybridization signal in only one chromosomal arm, whereas four chromosome pairs did not show any hybridization. These results are in agreement with previous GISH studies, which have identified the genomic source of the chromosomes involved in the meiotic configurations of Z. perennis × maize hybrids. These findings allow postulating that maize has a parental genome not shared with Z. perennis, and the existence of intergenomic restructuring between the parental genomes of maize. Moreover, the absence of hybridization signals in all maize knobs indicate that these heterochromatic regions were lost during the Z. perennis genome evolution.